Ear Rachis Xylem Occlusion and Associated Loss in Hydraulic Conductance Coincide with the End of Grain Filling for Wheat - Neghliz, Hayet; Cochard, Hervé; Brunel, Nicole; Martre, Pierre (Frontiers in Plant Science, 2016)
Seed dehydration is the normal terminal event in the development of orthodox seeds and is physiologically related to the cessation of grain dry mass accumulation and crop grain yield. For a better understanding of grain dehydration, we evaluated the hypothesis that hydraulic conductance of the ear decreases during the latter stages of development and that this decrease results from disruption or occlusion of xylem conduits. Whole ear, rachis, and stem nodes hydraulic conductance and percentage loss of conductivity were measured from flowering to harvest-ripeness on bread wheat (Triticum aestivum L.) cv. Récital grown under controlled environments. Flag leaf transpiration, stomatal conductance, chlorophyll content and grain and ear water potentials were also measured during grain development. We show that grain dehydration was not related with whole plant physiology and leaf senescence, but closely correlated with the hydraulic properties of the xylem conduits irrigating the grains. Indeed, there was a substantial decrease in rachis hydraulic conductance at the onset of the grain dehydration phase. This hydraulic impairment was not caused by the presence of air embolism in xylem conduits of the stem internodes or rachis but by the occlusion of the xylem lumens by polysaccharides (pectins and callose). Our results demonstrate that xylem hydraulics plays a key role during grain maturation.